Queerly Inside and Out in School…A Conversation - Keener, Terrah (Paideusis, 2014)
“Queerly Inside and Out in School ... A Conversation” draws upon the research from See Me, Hear Me ... Queerly Visible: Conversations About Family and School with Non-Heterosexual Parents and Their Children (Keener, 2012) that explored the schooling experiences of non-heterosexual parents and their children in Nova Scotia. Leveraging visual arts and performance as both a means of data generation and data representation, the generated artifacts illustrated how dominant cultural practices and narratives surrounding school and family perpetuate heteronormative ideology, while excluding and silencing non-heterosexual parents and their children. Queer visibility became a re-occurring place of reflection and tension for parents as they re-told their stories of creating a queer family presence in their child’s school. The stories represented within this paper provide a window into the experience of parents and children who on a daily basis run the risk of not being “seen” by their teachers, school administrators, and the broader school community.